2017
DOI: 10.1103/physrevx.7.021016
|View full text |Cite
|
Sign up to set email alerts
|

Hot Electrons Regain Coherence in Semiconducting Nanowires

Abstract: The higher the energy of a particle is above equilibrium, the faster it relaxes because of the growing phase space of available electronic states it can interact with. In the relaxation process, phase coherence is lost, thus limiting high-energy quantum control and manipulation. In one-dimensional systems, high relaxation rates are expected to destabilize electronic quasiparticles. Here, we show that the decoherence induced by relaxation of hot electrons in one-dimensional semiconducting nanowires evolves nonm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Yet, we emphasize that the injection and coherent propagation (over several microns) of hot carriers in two-dimensional electron gases was recently achieved [44]. Furthermore, it has just been shown that high-energy carriers retain their coherence when excited far enough above the Fermi sea [45]. Moreover τ i is in the range of 1-100 ps in graphene [46] and bilayer graphene [47] at a temperature of around 1K, suggesting the implementation of an electronic QTM to be feasible.…”
Section: Many-body Effectsmentioning
confidence: 82%
“…Yet, we emphasize that the injection and coherent propagation (over several microns) of hot carriers in two-dimensional electron gases was recently achieved [44]. Furthermore, it has just been shown that high-energy carriers retain their coherence when excited far enough above the Fermi sea [45]. Moreover τ i is in the range of 1-100 ps in graphene [46] and bilayer graphene [47] at a temperature of around 1K, suggesting the implementation of an electronic QTM to be feasible.…”
Section: Many-body Effectsmentioning
confidence: 82%
“…1(a), were grown in the <111> direction on an epi-ready (001) InAs substrate [17]. The nanowires have an hexagonal cross section obtained by low temperature growth procedure subsequent to the growth of the nanowires [18]. Epitaxial deposition of Al was carried out in-situ at room-temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[7], while peculiar features of the relaxation of very hot electrons were observed in Ref. [8]. These experiments have demonstrated the crucial role of the curvature of the spectrum of electrons.…”
mentioning
confidence: 70%